Orderly and disorderly practices of personal pronouns during Question Time in the Malaysian House of Representatives - David, Yoong (Journal of Modern Languages, 2011)
It is common practice in parliaments around the world for Members of Parliament (MPs) to address each other indirectly through the Speaker of the House while parliament is in session. Indeed, this practice is enforced in written law. Theoretically, failing to take heed of this rule can result in negative repercussions for the offending MP. This paper which incorporates the dimensions of orderliness and disorderliness of interaction, analyses the ways MPs and the Chair practise personal pronouns during Question Time in the Malaysian House of Representatives. Data which date from August to December 2006 are comprised of 43 Hansard transcripts and 54.5 hours of video recordings of Question Time. It is discovered that the majority type of personal pronouns is in first person, followed by third person pronouns. In stark contrast, second person pronouns occur very rarely. These findings indicate that MPs generally understand the expected norms of behaviour. Analysis also reveals that second person pronouns are sometimes used to deliberately flaunt parliamentary regulations to achieve specific objectives.